Epistemologia cognitiva para o uso de preposições: o caso da preposição de - Pedro Perini Frizzera da Mota Santos (2006)
This dissertation aims to present an analysis for the utterances of the preposition de in Brazilian Portuguese, using for this purpose, theoretical models proposed by COGNITIVE GRAMMAR and CONSTRUAL GRAMMAR. The hypothesis I claim is that prepositions arelinguistic forms, whose evolution can be at least partially mapped by itsGRAMATICALIZATION process. This research sustains that the original meaning of the preposition we analyze is a spatial one. To prove that hypothesis, theorical approaches, in particular the evaluation of the cognitive grammar as a pos-structuralism model, analysis of electronic corpora and experiments have been done. Empirical results provided, weface questions concerning the definition of preposition and its particularities in Brazilian Portuguese usage.